Microneedle Sensors for Multiplex Applications: Toward Advanced Biomedical and Environmental Analysis. Issue 2 (13th December 2022) - Omar, Rawan; Zheng, Youbin; Wang, Jing; Haick, Hossam
Abstract: Microneedles (MNs) are versatile tiny devices that have attracted interest in various fields including medicine, environment, food and agriculture due to their unique properties, such as low‐cost, simplicity, pain‐free application and minimally invasive penetration, therapeutic efficacy, biosensing ability, and biocompatibility. These properties along with the MNs distinctive geometry including dimension control, material type and fabrication techniques have enabled the optimization of MNs based on each desired application. This review summarizes the latest advances in MN‐based sensors in a variety of fields and provides a bird's eye view over the wide range of applications, starting from material and fabrication techniques to advanced sensor types in the biomedical and environmental fields for both sensing and treatment, and showing the profound advantages of this emerging tool in clinical and sustainable fields. Abstract : This review summarizes the latest developments in microneedle‐based sensors and provides a comprehensive overview of the wide range of applications, ranging from materials and fabrication techniques to advanced sensor types in the biomedical and environmental fields, demonstrating the tremendous advantages of this emerging tool for clinical and sustainability related applications.